Effects of ganglioside GM1 and erythropoietin on spinal cord injury in mice: Functional and immunohistochemical assessments - Torelli, Alessandro Gonzalez; Cristante, Alexandre Fogaça; Barros-Filho, Tarcísio Eloy Pessoa de; Santos, Gustavo Bispo dos; Morena, Beatriz Cintra; Correia, Felipe Fernandes; Paschon, Vera (Clinics, 2022)
Objectives: To evaluate the functional and immunohistochemical effects of ganglioside GM1 and erythropoietin following experimental spinal cord injury.Methods: Thirty-two male BALB/c mice were subjected to experimental spinal cord injury using the NYU Impactor device and were randomly divided into the following groups: GM1 group, receiving standard ganglioside GM1 (30 mg/kg); erythropoietin group, receiving erythropoietin (1000 IU/kg); combination group, receiving both drugs; and control group, receiving saline (0.9%). Animals were evaluated according to the Basso Mouse Scale (BMS) and Hindlimb Mouse Function Score (MFS). After euthanasia, the immunohistochemistry of the medullary tissue of mice was analyzed. All animals received intraperitoneal treatment.Results: The GM1 group had higher BMS and MFS scores at the end of the experiment when compared to all other groups. The combination group had higher BMS and MFS scores than the erythropoietin and control groups. The erythropoietin group had higher BMS and MFS scores than the control group. Immunohistochemical tissue analysis showed a significant difference among groups. There was a significant increase in myelinated axons and in the myelinated axon length in the erythropoietin group when compared to the other intervention groups (p < 0.01).Conclusions: Erythropoietin and GM1 have therapeutic effects on axonal regeneration in mice subjected to experimental spinal cord injury, and administration of GM1 alone had the highest scores on the BMS and MFS scales.